Implementation Of Internal Quality Assurance System In Order To Improve The Quality Of Polytechnical Research - Arifudin, Opan; Trisnamansyah, Sutaryat; Hanafiah; Sauri, R. Supyan (International Journal of Social Science, Education, Communication and Economics, 2022)
This research is motivated by the weak competence of lecturers in obtaining research grants, institutional support in providing budgets that are still inadequate, and the fulfillment of research criteria is still weak in supporting the accreditation of Polytechnics. This research approach is a qualitative research with case study method. The results of this study indicate that the determination in order to improve the quality of polytechnic research has been carried out but there is no specific policy on the research. The implementation of the internal quality assurance system in research has been carried out by monitoring the grants received by lecturers by looking at the outputs or publications. Evaluation of the internal quality assurance system in the study was carried out by means of an internal quality audit (AMI) which was held once a year to see the publications of each department. Control of the internal quality assurance system in the study was carried out by administrative control including the collection of SKP, BKD and AMI audits. The achievement of research Quality Standards that have been established through the application of SPMI is based on two main principles: continuous process improvement/improvement and continuous improvement of quality standards.